Prognostic Factors for Mortality of Pediatric Burn Injury in a National Tertiary Referral Center - Angkoso, Heru; Kekalih, Aria (UI Scholars Hub, 2022)
Introduction. In Indonesia, burn injuries cause about 195,000 deaths annually. Data from the Ministry of the Health Republic of Indonesia showed the incidence of burns predominated at 1-4 years old. The mortality of pediatric burn patients in a tertiary hospital was 37.26%. This study aimed to find an association between known and unknown prognostic factors of mortality in Indonesian-specific characteristics. Method. A retrospective analytical study included all pediatric burns admitted to Dr. Cipto Mangunkusumo General Hospital (CMGH) from 1998 to 2010. Variables within a period of the first 72 hours of admission were the focus of interest and were extracted from the medical record. Results. Of 609 pediatric burns, the mortality rate is 37.8%. Some contributing variables significantly associated with the mortality were TBSA, inhalation injury, length of hospitalization, hemoglobin 0-h level, hematocrit 24-h, and 48-h level, INR 0-h, and 48-h, fluid balance 24-h, base deficit, serum lactate, pulmonary edema, systemic inflammatory response syndrome (SIRS) + multiorgan failure (MOF), and acute coronary syndrome (ACS) (p <0.05). On multivariate analysis, the significant variable was length of hospitalization <14 days, SIRS+MOF, abnormal hematocrit 0-h level, and abnormal serum lactate level. Conclusion. The more identified prognostic factors a patient finds, the more the mortality risk. In addition, excessive fluid resuscitation leads to a high likelihood of pulmonary edema, SIRS+MOF, and ACS complications, followed by increased mortality risk